BENEATHA'S FEMINISM PERSPECTIVES TOWARD MODERN BLACK WOMEN IN LORRAINE HANSBERRY'S A RAISIN IN THE SUN - Ayu Meilani Saraswati (Humaniora Scientia, 2018)
This research discusses Beneatha's feminism perspectives toward modern black women. The aims of this research are to find out the Beneatha's feminism perspectives toward modern black women based on Lorraine Hansberry's A Raisin in the Sun and to discover the causes that make Beneatha have different feminism perspectives toward other black women. Library research was conducted to collect the data. The data consist of the ideas related to Beneatha's feminism perspectives toward modern black women in Lorraine Hansberry's A Raisin in the Sun. In addition, the theories used in this research were the theories of feminism, radical feminism, oppression, and gender role. The approaches used are psychological approach, sociological approach, and moral approach. The data analysis shows as follows: Beneatha wants to be equal with the position of the men, willing to be a stronger woman as the result of being oppressed by male supremacy, wants to be different from the other black women, wants to be honored by the man, and confronts the male power. Furthermore, after analyzing those problems, the researcher found that as a woman she has to struggle to get the same right as a man. The woman has to have a bravery to do what she wants.